(untitled) - Goold, Michael (New York, 1994)
Advance praise for Corporate-Level Strategy. "At last a book that cuts through all the corporate jargon and academic generalizations to answer the question 'Does the corporate parent create or destroy value for the organization?' The authors suggest a simple yet compelling framework for making this determination. Must reading for students and practitioners alike." -Robert Cizik Chairman and Chief Executive Officer Cooper Industries "In an era when the role of corporate-level management is quite justifiably being questioned and challenged, it is refreshing to find a book that clearly shows how parent companies can add rather than destroy value in their businesses.
Keywords: Conglomerate corporations,Tổng công ty